Stewart and Kincaid, Irish land agents in the 1840s - Desmond A. G. Norton (University College Dublin, Department of Economics, 2002)
Drawing on a recently-discovered correspondence archive of the 1840s, this article describes activities of the then most important land agency in Ireland, Messrs Stewart and Kincaid. Several of the firm's clients resided in England. The partners supervised major agricultural improvements. They also implemented programmes of assisted emigration during the great Irish famine. The correspondence yields new insights into economic and social conditions in Ireland during the forties. It undermines popularly-held views of such conditions and suggests need for revision of findings of modern historians.
hdl:10197/1286
Keywords: 330; Boden; Makler; Wirtschaftsgeschichte; Irland